Synthesis, Characterization, and Adsorptive Performance of Ag-Doped ZnO Nanoparticles for Melanoidin Removal - Mehwish Qaseem; Saeed Ahmad; Muhammad Yasir Khan; Muhammad Wasim Akhtar; Muhammad Furqan Ali; Muhammad Saquib Ali; Shakeel Ahmed; Shahid Bhutto; Mehwish Altaf (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
Melanoidin, a complex polymer compound formed through Maillard reactions during fermentation, constitutes a significant fraction of distillery wastewater and cannot be treated using standard treatment methods. Silver doped zinc oxide nanoparticles (AgZnONPs) were synthesized, characterized, and used in this work as potential adsorbent to remediate melanoidin from aqueous solutions. The as-synthesized nanoparticles were evaluated using X-ray diffraction (XRD), UV-visible spectroscopy, field-emission scanning electron microscopy (FE-SEM) with energy-dispersive X-ray spectroscopy (EDX), and Fourier-transform infrared spectroscopy (FTIR). Adsorption experiments were performed under varying operational parameters, including solution pH, mass of adsorbent, initial melanoidin concentration, and time of contact. Under optimal conditions, pH 7, 0.5 g/L adsorbent, 200 mg/L of adsorbate concentration, and 90 min contact duration, a maximum removal efficiency of 92% was achieved. The enhanced adsorption performance aligns with the Langmuir isotherm approach, demonstrating monolayer adsorption with a 50 mg/g maximum adsorption capacity. It adheres to pseudo-second-order kinetics, providing strong evidence of chemisorption with a rate-limiting mechanism and predominant process. These results illustrate the potential of AgZnONPs as a robust and efficient adsorbent material for the treatment of melanoidin-rich distillery effluents.